Pengaruh Profesi Orang Tua terhadap Motivasi Belajar Siswa untuk Melanjutkan Sekolah ke Jenjang yang Lebih Tinggi: Studi Kasus: Seluruh Siswa SMPN 2 Kalidawir Kabupaten Tulungagung - Sibit Werda Anugrah Kinasen; Jani Jani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research is based on the problem of students' interest in continuing school after graduating from junior high school at SMPN 2 Kalidawir which is based on observation and question-and-answer time with the teaching teacher. The busy work of parents and without monitoring the child's learning process makes the child less focused and less concerned about his future and tends to choose work rather than continue school. This is due to the lack of motivation from the closest family and the surrounding environment. The formulation of the problem obtained by the author is how the influence of the parental profession on the motivation of students to continue school to a higher level. From the formulation of the problem, the author's goal is to determine the influence of the parental profession on the motivation of students to continue school to a higher level. This research includes quantitative research, and the type of research used is associative. The object of this study is all students of SMPN 2 Kalidawir for the 2023/2024 school year with a population of 249 students and a sample of 25 students. Data collection techniques using questionnaires. Data analysis techniques through instrument data tests, prerequisite tests, and hypothesis tests using simple regression analysis. The results showed: there was a significant positive and significant relationship between the parents' professions on students' learning motivation, and there was a significant influence between parents' professions on students' learning motivation. This is evidenced by the results of a simple regression analysis from the ANOVA table obtained a value of 0.000. Based on the decision-making guidelines, if the significance value < 0.05, it means that variable X affects variable Y. The conclusion is 0.000 < 0.05, which means that variable X has a significant effect on variable Y. Based on the hypothesis, H1 is accepted and H0 is rejected